(untitled) (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. This article aims to analyze some examples of solidarity and cooperation between Portuguese cultural institutions, enterprises, artists, workers, volunteers, and local communities during the Covid-19 crisis. The research will focus on the years 2020 and 2021. Approach/methodology. Our approach to the subject matter encompasses four main components. One is an in-text glossary to clarify a few concepts in view of national legislation. The second is a brief contextualization of the evolution of the pandemic at an (inter)national level. The third one is a description of how cultural institutions, heritage sites, and professionals were affected by the widespread virus. And the fourth one is the analysis of five case studies of actions of solidarity and cooperation within the cultural field. Findings. Thanks to our research, we distinguish the negative impacts of Covid-19 from pre-existent problems in the sector. We have also found that some initiatives created to support cultural heritage may be questionable. Since the sanitary crisis is not over yet, the research is limited to the current state of knowledge. Future exploration on the matter may be relevant to find new case studies and consequences of the pandemic. We believe this article can have a social impact since it promotes a reflection on the economic sustainability, social engagement, and ethical responsibilities of cultural institutions and stakeholders. Besides, the discussion about the vulnerable conditions in which cultural workers found themselves during this crisis is of utmost urgency to design a better future for the sector and those who keep it running. Originality. The originality of our study lies in the registration of creative strategies found to counteract the outcomes of the pandemic, which may be inspiring in future times of emergency.